Maturity level of digital twins applied to buildings with cultural value: the foyer and smoking rooms of the National Theater of Costa Rica - Bulgarelli-Bolaños, Jose Pablo (2025)
This paper describes the results of the process with which it was possible to define the degree of maturity of a Digital Twin (DT) for real estate with cultural value, determining that this level can be communicative with interactive functionalities; this within the framework of a research project, whose case study is the foyer and smokers of the National Theater of Costa Rica, where one of its results was the definition of the requirements and scope for the future development of the DT. The methodology includes a documentary analysis of the scientific production published from 2019 and until 2024 on the subject, in journals indexed in Web of Science and Scopus, within the framework of the Architecture, Engineering and Construction industry; results that were contrasted with the expectations of the custodian of the case study. Based on this and according to the technology available at the time of the research, the maturity level that the research team defined as the possible level to reach in the tool development process was specified.